Environmental Influence of Gas Flaring: Perspective from the Niger Delta Region of Nigeria - Kingsley Eghonghon Ukhurebor; Uyiosa Osagie Aigbe; Robert Birundu Onyancha; Hussain Athar; Benedict Okundaye; Paul Atagamen Aidonojie; Benita Ebindu Siloko; Ismail Hossain; Heri Septya Kusuma; Handoko Darmokoesoemo (Geofluids)
Gas flaring (GasF) is an important aspect of the combustion mechanisms in the burning of related, undesirable, or surplus fluids (gases in particular) that are released during the ordinary or unexpected overpressuring process in several industrial activities, specifically in the petroleum resource (PTR) industries. It is also one of the major sources of greenhouse gas emissions which cause climate change (CMC). In addition to the generation of noise and heat, it makes substantial adjacent areas uninhabitable and, hence, causes detrimental consequences to the entire ecosystem as well as waste energy and results in economic losses. Reducing GasF is a critical issue due to its ensuing complications; consequently, there is a tenacious need to measure GasF via the study of its composition, distribution, and capacity, as well as the utilization of appropriate GasF recovery/removal procedures. The present review study will, thus, attempt to assess the impacts of GasF on the environment vis-à-vis the possible nexus between GasF/CMC using the perspective of the Niger Delta region of Nigeria which is rich in PTR, with relevant information drawn from existing publications. The roles of government, policymakers, and relevant stakeholders as well as suggestions and recommendations that will assist in the extenuation approaches and technologies of the influence of GasF on the environment are also discussed.